2021
DOI: 10.1038/s43018-021-00219-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy induces canalization of cell state in childhood B-cell precursor acute lymphoblastic leukemia

Abstract: Comparison of intratumor genetic heterogeneity in cancer at diagnosis and relapse suggests that chemotherapy induces bottleneck selection of subclonal genotypes. However, evolutionary events subsequent to chemotherapy could also explain changes in clonal dominance seen at relapse. We, therefore, investigated the mechanisms of selection in childhood B-cell precursor acute lymphoblastic leukemia (BCP-ALL) during induction chemotherapy where maximal cytoreduction occurs. To distinguish stochastic versus determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 74 publications
(72 reference statements)
4
39
1
Order By: Relevance
“…Of note, since SNP-arrays are limited in both genomic resolution (i.e., deletion size) and sensitivity to low abundance copy number variants (CNV) it is possible that our model might underestimate the number of clones (Figure 2B and supplementary methods). Nonetheless, this finding clearly illustrates the high clonal complexity of ALL and is in line with our earlier single-cell WGS based characterization of genetic heterogeneity in non-Down Syndrome ALL, which also identified branching clonal architectures with up to 19 descendant subclones 6 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Of note, since SNP-arrays are limited in both genomic resolution (i.e., deletion size) and sensitivity to low abundance copy number variants (CNV) it is possible that our model might underestimate the number of clones (Figure 2B and supplementary methods). Nonetheless, this finding clearly illustrates the high clonal complexity of ALL and is in line with our earlier single-cell WGS based characterization of genetic heterogeneity in non-Down Syndrome ALL, which also identified branching clonal architectures with up to 19 descendant subclones 6 .…”
Section: Resultssupporting
confidence: 89%
“…In studies of childhood acute lymphoblastic leukaemia (ALL), we and others previously used multicolour-FISH and whole genome sequencing to show that these tumours are clonally variegated, and to demonstrate through serial transplantation assays, that leukaemia tumour propagating cells (TPCs) are also genetically heterogeneous 4,5 . This finding was supported by our later genetic analysis of immunophenotypically distinct ALL diagnostic subpopulations which demonstrated similar distribution of subclones within a disease-specific primitive B-cell compartment (stemB, 34 + 38 - 19 + ) and the disease bulk in most but, crucially, not all leukaemias 6 . Such experiments relied on high-depth bulk whole-genome sequencing followed by single-cell qPCR and, together with our earlier work, suggested that genotype and phenotypes related to differentiation stage and cell-cycle state might not necessarily co-segregate within the disease.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Such a phenomenon, where plasticity first allows the individuals (here, cancer cells) to explore the phenotypic space before adaptive traits (e.g., drug resistance) are enforced by heritable genetic or epigenetic alterations, is reminiscent of the 'Baldwin effect' in evolutionary biology [49]. A similar phenomenon has recently been described in childhood B-cell precursor acute lymphoblastic leukemia [50]. Indeed, transient changes involved in drug resistance have been reported to occur in vivo [51] and ex vivo [52], which may allow a subset of AML cells to survive long enough time to acquire heritable resistance (epi)mutation [43].…”
Section: Functional Identitymentioning
confidence: 93%
“…For this potential application to be successful, we require that the emerging populations are uniquely marked by a number of SCNAs. In some cases, treatment response appears to be driven by ''phenotypic plasticity'' where cellular behavior changes without underlying genetic change (Turati et al, 2021;Shaffer et al, 2017). This scenario violates a key assumption of liquidCNA that the emerging population is dominated by a subclone of distinct karyotype, and so we would expect the application of liquidCNA to fail.…”
Section: Limitations Of Studymentioning
confidence: 99%